Implementación de un sistema eléctrico industrial de tipo trifásico 220V de 125kVA para la empresa STERILIZE SERVICE S.A.S en el municipio de Sandoná -Nariño - Cupacan Quiñonez, Ronaldo; Unigarro Oñate, Wilson Fernando (Universidad Antonio Nariño, 2022)
An electrical design is required industry and its implementation, with a power of 125kVA three-phase system for the company Sterilize Service. The installation will be carried out in the urban area of ​​the municipality of Sandoná-Nariño carrying out the concept of new work, according to the criteria of the facilities technical regulations (RETIE) and the NTC 2050, which is of a Required for all electrical work. According to the ministry of mines and energy. The project will benefit the company by guaranteeing the continuity of production, avoiding unforeseen stoppages due to internal electrical faults; It will also improve the safety of equipment and workers. Inside the installation plan the assembly of the transformer will not be carried out since this activity was taken over by another company.